(untitled) (International Journal of Innovative Technologies in Economy, 2024)
Investment is the inclusion of a certain amount of money in a way to be able to add value or pass on the right return (Sutha, 2000). This research aims to understand fundamental analysis and technical analysis needed to make investment decisions. The motivation in this study is to find out the price of the stock purchased and analyze the stock using fundamental analysis and technical analysis. The research methods required from this study are secondary data sourced from historical data, income statements and balance sheets from investing.com 2019-2022, technical analysis sourced from weekly reports dated October 23-27, 2023, the RTI Business application to view stock charts, and data sourced from the siminvest application for buying and selling stock on the siminvest application. The samples used for this study are samples of company stocks sourced from the siminvest application, namely BUKA, GOTO, EMTK, and SIDO. The results showed that in the fundamental analysis on EPS, PER, ROE, DER stock BUKA, GOTO, ETMK, and SIDO increased and decreased. ROA on BUKA stock has increased and ROA on GOTO, ETMK, SIDO stocks has increased and decreased. In technical analysis, GOTO’s stock selling price suffered a loss and the stock selling price profited. In EMTK and SIDO stocks just bought shares. In BUKA stock obtained stock returns of 0.0294117, 0.01960784, -0.01941474, in GOTO stock, obtained stock returns of 0.015625 and -0.01538461, in EMTK stock obtained returns of -0.009009009 and in SIDO stock experienced returns of 0.